2022
DOI: 10.1101/2022.07.15.500201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic map of the most recent evidence (2010 to 2019) on ruminant production-limiting disease prevalence and associated mortality in Ethiopia

Abstract: Ethiopia’s livestock sector supports the livelihoods of millions of smallholder farmers. However, despite the improvements of recent years, livestock productivity remains low due to critical constraints, including infectious diseases. The aim of this study was to collate and synthesise the published evidence on ruminant disease frequency and disease-associated mortality in Ethiopia, by identifying knowledge gaps and clusters in the literature to provide the basis for a decision-making tool. Searches on both bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…That there was evidence of spatiotemporal variation of risk factors and causes of mortality is not surprising, as seasonal and environmental variation affects grazing availability and ensuing movement and mixing of animals ( 31 , 34 , 35 ) which can then affect disease transmission. A recent systematic review observed a scarcity of disease-associated mortality data for Ethiopia, with only 14 studies identified [( 36 ), under review]. Droughts occur frequently in Ethiopia, causing severe damage and harm.…”
Section: Discussionmentioning
confidence: 99%
“…That there was evidence of spatiotemporal variation of risk factors and causes of mortality is not surprising, as seasonal and environmental variation affects grazing availability and ensuing movement and mixing of animals ( 31 , 34 , 35 ) which can then affect disease transmission. A recent systematic review observed a scarcity of disease-associated mortality data for Ethiopia, with only 14 studies identified [( 36 ), under review]. Droughts occur frequently in Ethiopia, causing severe damage and harm.…”
Section: Discussionmentioning
confidence: 99%
“…That there was evidence of spatiotemporal variation of risk factors and causes of mortality is not surprising, as seasonal and environmental variation affects grazing availability and ensuing movement and mixing of animals (Devereux, 2006; Getachew et al, 2010; Gelalcha et al, 2021) which can then affect disease transmission. A recent systematic review observed a scarcity of disease-associated mortality data for Ethiopia, with only 14 studies identified (Tsouloufi et al, 2022, submitted). In our study’s semis-tructured interviews, a key informant reported drought as one of the major causes for mortality and reproductive losses in cattle and small ruminants, with peak mortality with the first rains following drought.…”
Section: Discussionmentioning
confidence: 99%
“…Observational (cross-sectional or cohort) studies that reported on the incidence and/or prevalence or mortality of selected infectious diseases affecting Ethiopian ruminants (cattle, sheep or goats) were considered for inclusion. The specific diseases to be studied were chosen based on experts' opinion, and the existing literature, the method was described fully in the map protocol ( 21 ). Experimental studies, preliminary or pilot studies, studies that report on aggregated livestock data or outbreaks, studies which cover non-infectious diseases or other conditions (e.g., drought), as well as case report/series studies were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A copy of the Systematic map evidence base in the form of an excel file is stored on the Edinburgh DataShare platform ( 21 ). Thereby ensuring the long-term storage of the evidence base and allowing a persistent Digital Object Identifier (DOI) to be provided.…”
Section: Methodsmentioning
confidence: 99%